Urinary concentrations of biomarkers of phthalates and phthalate alternatives and IVF outcomes. (February 2018) - Machtinger, Ronit; Gaskins, Audrey J.; Racowsky, Catherine; Mansur, Abdallah; Adir, Michal; Baccarelli, Andrea A.; Calafat, Antonia M.; Hauser, Russ
Abstract: Phthalates are a class of chemicals found in a large variety of consumer products. Available experimental and limited human data show adverse effects of some phthalates on ovarian function, which has raised concerns regarding potential effects on fertility. The aim of the current study was to determine whether urinary concentrations of metabolites of phthalates and phthalate alternatives are associated with intermediate and clinical in vitro fertilization (IVF) outcomes. We enrolled 136 women undergoing IVF in a Tertiary University Affiliated Hospital. Participants provided one to two urine samples per cycle during ovarian stimulation and before oocyte retrieval. IVF outcomes were abstracted from medical records. Concentrations of 17 phthalate metabolites and two metabolites of the phthalate alternative di(isononyl) cyclohexane-1, 2-dicarboxylate (DINCH) were measured. Multivariable Poisson regression models with log link were used to analyze associations between tertiles of specific gravity adjusted phthalate or DINCH metabolites and number of total oocytes, mature oocytes, fertilized oocytes, and top quality embryos. Multivariable logistic regression models were applied to evaluate the association between tertiles of specific gravity adjusted phthalate or DINCH metabolites and probability of live birth. Urinary concentrations of the sum of di-2-ethylhexyl phthalate metabolites (∑ DEHP) and the individual metabolites mono-2-ethyl-5-hydroxyhexyl phthalate, mono-2-ethyl-5-oxohexyl phthalate, and mono-2-ethyl-5-carboxypentyl phthalate were negatively associated with the number of total oocytes, mature oocytes, fertilized oocytes, and top quality embryos. Of the low molecular weight phthalates, higher monoethyl phthalate and mono- n -butyl phthalate concentrations were associated with significantly fewer total, mature, and fertilized oocytes. None of the urinary phthalate metabolite concentrations were associated with a reduced probability implantation, clinical pregnancy or live birth. Metabolites of DINCH were not associated with intermediate or clinical IVF outcomes. Our results suggest that DEHP may impair early IVF outcomes, specifically oocyte parameters. Additional research is needed to elucidate the potential effect of DEHP on female fertility in the general population. Highlights: We examined the associations between phthalates and phthalate alternative metabolites and IVF outcomes. Exposure to ∑ DEHP metabolites, MEP and MnBP was inversely associated with number of oocytes retrieved and fertilized. We did not find associations between phthalate and phthalate alternative metabolites and IVF clinical outcomes.